Cinobufagin-Loaded and Folic Acid-Modified Polydopamine Nanomedicine Combined With Photothermal Therapy for the Treatment of Lung Cancer - Li, Jianwen; Zhang, Zhanxia; Deng, Haibin; Zheng, Zhan (Frontiers in Chemistry, 2021)
Cinobufagin is used as a traditional Chinese medicine for cancer therapy. However, it has some disadvantages, such as poor water solubility, short circulating half-life, and low bioavailability. In the present study, a targeted delivery and smart responsive polydopamine (PDA)-based nanomedicine for delivering cinobufagin was rationally designed to improve the anticancer efficacy of the compound for the treatment of lung cancer. The modification of the nanomedicine using folic acid first mediated tumor targeting via the interaction between folic acid and its receptors on tumor cells. After lysosomes escape, the PDA nanomedicine was triggered by the low pH and released its cargo into the tumor microenvironment. The nanomedicine had a better therapeutic effect against lung cancer when used in combination with photothermal therapy. Compared with other nanomedicines used with photothermal therapy, this nanocarrier was not only sensitive to biologically low pH levels for on-demand drug release, but was also biodegradable, breaking down into biocompatible terminal products. Therefore, the proposed drug delivery system with targeted delivery and smart release demonstrated potential as a multifunctional nanoplatform that can enhance the bioavailability and reduce the side effects of chemotherapeutic agents.